Pengaruh Penggunaan Teknologi Terhadap Perkembangan Kemampuan Berbahasa Indonesia pada Generasi Milenial - Rizki Fitriani; Nadella Lesmana (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to investigate the impact of technology usage on the development of Indonesian language skills among the millennial generation. Millennials are a group that has grown up in a rapidly advancing digital technology era, which significantly affects their ways of learning and communicating, including in language aspects. By utilizing survey and interview methods, data were collected from a representative sample of millennials who actively use technology. The results of the study indicate that the use of technology, such as smartphones, social media, and online learning platforms, has a significant impact on the development of Indonesian language skills among millennials. Although technology provides easy access to information and learning resources, this research also highlights several challenges, such as the misuse of language on social media, which can negatively affect both written and oral language skills. The implications of these findings offer valuable insights for educators, parents, and policymakers in designing effective language learning strategies for the millennial generation.